A significant hepatotoxicity associated with paracetamol overdose in the absence of kidney injury in rabbits - Ahmed, Jawad Hassan (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Overdose of paracetamol (PCM) is reported to cause hepatotoxicity and nephrotoxicity, or nephrotoxicity in absence of hepatotoxicity. This study was planned to investigate hepatotoxicity or nephrotoxicity induced by PCM. Methods: Two groups of rabbits, six rabbits in each were used; control group were treated with normal saline, the second group was treated with PCM 1 g/kg/day orally for 9 days. Results: PCM lead to a significant rise in serum liver enzymes, aspartate aminotransferase, alanine transaminase, alkaline phosphatase and total bilirubin with an increase in serum level of malondialdehyde (MDA) and reduction in serum glutathione (GSH). MDA level in liver homogenate was also significantly increased. These findings were further confirmed by histopathological changes suggestive of severe liver damage. On the contrary, PCM slightly increased serum creatinine, without changing MDA and GSH in kidney homogenate. Lack of PCM nephrotoxicity was further confirmed by histopathological examination. Conclusion: PCM overdose produced severe hepatotoxicity without affecting the kidneys of the rabbits